A review of school trauma-informed practice for Aboriginal and Torres Strait Islander children and youth. (11th July 2020) - Miller, Jenna; Berger, Emily
Abstract: Aboriginal and Torres Strait Islander people in Australia are especially vulnerable to traumatic and discriminatory experiences. However, limited literature and research has implemented and evaluated school-based interventions designed to assist Aboriginal and Torres Strait Islander children and young people to overcome their adversity and achieve their potential at school. This article reviews the literature and frameworks on school programs designed for Aboriginal and Torres Strait Islander students who have experienced trauma. The key aspects of trauma-informed programs in schools for Aboriginal and Torres Strait Islander students is explored and recommendations made for further research and greater acknowledgement of cultural and historical issues for Aboriginal and Torres Strait Islander students when implementing culturally informed and trauma-informed practices in schools.